Sources of Disaster: A Roundtable Discussion on New Epistemic Perspectives in Post-3.11 Japan. Issue 4 (2nd October 2021) - Onaga, Lisa; Schieder, Chelsea Szendi; Buhrman, Kristina; Jacoby, Julia Mariko; Juraku, Kohta; Slater, David H.; Wiemann, Anna; Dekant, Alexander; Winter, Stella; Herzum, Jacob; McLaughlin, Levi; Ortiz, Angela Marie
Abstract: On 16 March 2021, the Teach311 + COVID-19 Collective (www.teach311.org ) hosted a virtual roundtable discussion entitled "Sources of Disaster: New Epistemic Perspectives in Post-3.11 Japan." The event brought together scholars and students researching the history and anthropology of Japan to explore how the earthquake, tsunami, and nuclear power plant disaster of 11 March 2011 (3.11) changed our ways of knowing the world. The roundtable focused on the idea of the "source" to get at these epistemic shifts in lived experience and practical knowledge as well as historiography, and to investigate ideas that range from what we can know about acceptable risk and safety to notions of home and belonging. "Source" is a way to think about origins, but also the materials—texts, media, or testimony—that we collect and analyze to give rise to new or better knowledge. Building upon previous Teach311 activities that explored the roots of 3.11 and genba, participants in this roundtable expanded upon the significance and meanings of the notion of a "source" relative to the politics of epistemology in their research and studies in order to examine what reconstruction means in history when it is conducted alongside recovery.